2015
DOI: 10.21608/jssae.2015.43204
|View full text |Cite
|
Sign up to set email alerts
|

MUTUAL EFFECT AMONG COMPOST AND FOLIAR SPRAYING WITH ZINC AND BORON ON SUGAR BEET (Beta vulgaris l.) GROWN ON SALINE SANDY LOAM SOIL

Abstract: Two field experiments were conducted at the village (7) in Gelbana, North Sinai Governorate, Egypt during two successive winter seasons of 2013/2014 and 2014/2015 to study the response of sugar beet (Mirodor) grown on saline sandy loam soil to study the interaction effect of compost, (CO) amendment and foliar spraying with micronutrients (Zn and B) solely or in combinations on some growth parameters, productivity and nutrients content in sugar beet roots. The obtained results reveal that CO and foliar applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
3
2
0
Order By: Relevance
“…Increasing sugar beet chemical constituents, yield components, quality and yields by foliar spraying with boron may be attributed to the role of boron in cell division and elongation in meristematic tissues, nitrogen metabolism and hormonal action (BARI, 2006), also boron had a vital role in sugar translocation to roots, therefore improve growth, yields and quality of sugar beet. These findings agree with Abo-Steet et al (2015) they found that CO and foliar application with Zinc and Boron enhanced the growth and yield productivity of sugar beet roots as well as nutrient contents and available N, P, K, Fe, Mn, Zn and B contents. Similar results were obtained by Abdel-Motagally (2015) who reported that foliar application with boron at a rate of 100 mg L -1 gave the highest sugar yield and the best technological quality.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Increasing sugar beet chemical constituents, yield components, quality and yields by foliar spraying with boron may be attributed to the role of boron in cell division and elongation in meristematic tissues, nitrogen metabolism and hormonal action (BARI, 2006), also boron had a vital role in sugar translocation to roots, therefore improve growth, yields and quality of sugar beet. These findings agree with Abo-Steet et al (2015) they found that CO and foliar application with Zinc and Boron enhanced the growth and yield productivity of sugar beet roots as well as nutrient contents and available N, P, K, Fe, Mn, Zn and B contents. Similar results were obtained by Abdel-Motagally (2015) who reported that foliar application with boron at a rate of 100 mg L -1 gave the highest sugar yield and the best technological quality.…”
Section: Discussionsupporting
confidence: 92%
“…Foliar spraying sugar beet plants with boron at a suitable rate depended on soil pH and boron content, significantly increased root length, root diameter, sucrose and juice purity percentages, root, top and sugar yields, however, Na, K, α-amino N, harvest index and loss sugar yield were decreased. Seeing as roots absorbed boric acid and the role of boron in chloroplast formation, sink limitations and changes in the cell wall, which lead to secondary effects in plant metabolism, development, growth and yield with good quality (Armin and Asgharipour, 2012;Abd El-Azez, 2014;El-Sheref, Amina, 2014;Abo-Steet, Seham et al, 2015;Abdel-Nasser andBen-Abdalla, 2019 andKandil et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These results are confirmed with those obtained by Abo-Steet et al, (2015) and Masri and Hamza (2015).…”
Section: -Effect Of Boron Fertilizationsupporting
confidence: 92%
“…Concerning the industrial sugar quality, foliar Zn 300 applied singly or in combination (Tables 4 and 5, Tables S2 and S3), significantly increased sucrose, PS, and purity, while the non-sugar contents (Na, K, α-amino N, and LS) were decreased compared to control (Zn 0 ). Similar trends are noted in [77,81,82]. These reports show that Zn improves sugar beet sugar quality (sucrose, PS, and purity) and reduces non-sugary elements under salinity conditions.…”
Section: Discussionsupporting
confidence: 77%